PENGARUH GREEN PRODUCT, GREEN PRICE, GREEN PLACE, GREEN PROMOTION TERHADAP KEPUTUSAN PEMBELIAN TUMBLER STARBUCKS TANGERANG - Ayu Dwi Lestari; Edy Nursanta; Widiyarsih Widiyarsih; Siti Masitoh (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
In the current era of globalization brings various changes that have an impact on aspects, especially on the environment. characterized by the occurrence of damage such as global warming (global warming) this is triggered by waste that is difficult to decompose such as plastic waste. So the Starbucks company is involved in implementing green marketing by producing Starbucks tumbler products to reduce plastic packaging. The purpose of this study was to analyze the effect of Green Product, Green Price, Green Place, Green Promotion on the Purchase Decision of Starbucks tumbler users.The analysis method in this study uses quantitative primary data, the test stages carried out are: validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression, F test, t test and coefficient of determination. The data used in this study used a questionnaire instrument, and the valid data collected were 100 respondents. The sampling method in this research is purposive sampling. The testing tool used is SPSS. The results of this study indicate that the variables Green Product, Green Price, Green Place, Green Promotion partially have a positive effect on purchasing decisions. While simultaneously the variables Green Product, Green Price, Green Place, Green Promotion have a positive and significant effect on the purchasing decisions of Starbucks tumbler users.